Prosecutorial Analytics - Jason Kreag (Washington University Law Review, 2017)
The institution of the prosecutor has more power than any other in the criminal justice system. What is more, prosecutorial power is often unreviewable as a result of limited constitutional regulation and the fact that it is increasingly exercised in private and semi-private settings as the system has become more administrative and less adversarial. Despite this vast, unreviewable power, prosecutors often rely on crude performance measures focused on conviction rates. The focus on conviction rates fails to capture and adequately evaluate the breadth of prosecutorial decision- making. We can do better by fully implementing analytics as a tool to evaluate the prosecutorial function. This tool has revolutionized crime- fighting. Yet, it has been conspicuously absent as a tool to improve other aspects of the criminal justice system. This Article demonstrates the promise of prosecutorial analytics to improve oversight and to promote systemic interests in justice, fairness, and transparency. It offers concrete examples of how analytics can 1) help eliminate race-based jury selection practices; 2) minimize prosecutorial misconduct; 3) uncover whether undesirable arbitrary factors shape prosecutorial discretion; and 4) provide better metrics for the judiciary, practitioners, and the public to evaluate prosecutorial performance.
Keywords: PROSECUTORIAL ANALYTICS; prosecutorial power; prosecutorial analytics; criminal justice; Batson v. Kentucky; prosecutor power